Memahami dinamika sosial dalam masyarakat - Hasanah, Maulidiyatul (Maliki Interdisciplinary Journal, 2025)
Social dynamics refer to the process of change occurring in the structure, values, norms, and interaction patterns of society as a response to internal and external factors. This article examines this phenomenon, focusing on the influence of globalization, technological advancements, and socio-economic changes in Indonesia. Key drivers such as value shifts, information technology, globalization, and social-political crises are identified as major contributors to social dynamics, resulting in both positive and negative impacts. Positive effects include social innovation, increased awareness, and social mobility, while negative impacts encompass social alienation, intercultural conflicts, and social inequality. The article also explores strategies for managing social dynamics, such as multicultural education, enhancing digital literacy, inclusive policies, community empowerment, and social research. By understanding social dynamics, effective public policies can be designed to foster an inclusive, harmonious, and sustainable society.